Evaluation of Nutritional and Antinutritional Properties of African Yam Bean (Sphenostylis stenocarpa (Hochst ex. A. Rich.) Harms.) Seeds - Taofeek T. Adegboyega; Michael T. Abberton; AbdelAziz H. AbdelGadir; Mahamadi Dianda; Busie Maziya-Dixon; Olaniyi A. Oyatomi; Sam Ofodile; Olubukola O. Babalola (Journal of Food Quality)
African yam bean (Sphenostylis stenocarpa (Hochst ex. A. Rich.) Harms) is an annual legume with the capacity to produce bean seeds in a pod and produce tubers with varying seed patterns and colors. It is suggested to have the potential to significantly boost food security in sub-Saharan Africa due to its considerable nutritional qualities but still yet underutilized. Many farmers show limited interest in its production owing to limited knowledge of its nutritional profile, income generation capacity for small-holder farmers’, processing, and other related utilization concerns. This study evaluated the proximate and antinutrient composition of processed and unprocessed seeds of African yam bean (Sphenostylis stenocarpa (Hochst ex. A. Rich.) Harms.). Seeds were harvested from the experimental research field consisting of 50 accessions at the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria. They were divided into two portions; the first was processed by oven drying at 60°C for 24 hours and the second was left raw. There were significant differences (P<0.05) in the levels of proximate and antinutrient in the forms in which the samples were analyzed. TSs104 had the highest protein content of 25.08%, while the lowest was TSs68 (20.50%). However, in the unprocessed seed, protein content ranged between 24.93% (TSs38) and 19.13% (TSs11). Both processed and unprocessed seeds had high carbohydrate contents. In processed seeds, TSs9 (62.93%) had the highest percentage and TSs1 (29.64%) recorded the lowest. In unprocessed seed, the percentage ranged between 67.36% (TSs4) and 54.23% (TSs38). The observed variation may suggest possible suitability of seed for various end-use products and targeted breeding programs for crop improvements. In sub-Saharan Africa, this lesser-known legume could be adapted as a promising food crop in combating protein-energy malnutrition.